The co-created boundary: negotiating the limits of coaching - Alison Maxwell (International Journal of Evidence Based Coaching and Mentoring, 2009)
This paper explores how business coaches experience the boundary between coaching and therapy in their practice. Using a phenomenological approach, four therapeutically trained and four non-therapeutically trained coaches were asked to describe instances when they felt they were working near the ‘boundary’. Findings suggest that issues of a psychological nature are brought into coaching, and that the ‘boundary’ is largely a function of the willingness and ability of both coach and client to work with personal/psychological material. Differences in working practice were noted between and within the two groups. Findings also give impetus for more rigorous coach training as well as suggesting a potentially fruitful tool for use in coach supervision.